Smart Apps Creator (SAC) Assisted Comic Media Development in Optimizing Visual Spatial Intelligence - Asri Wahyuni; Supratman Supratman; Puji Lestari (AlphaMath : Journal of Mathematics Education, 2023)
This study aims to produce SAC-assisted comic media and analyze the effectiveness and quality of using comics media to optimize students' visual-spatial intelligence. This research is a Research and Development (R&D) research using a 4D development model, which includes four stages: define, design, develop, and disseminate. In the "define" stage, the researcher did observations and interviews and distributed questionnaires to teachers and students. In the "design" stage, the researcher made prototypes of media development and visual-spatial intelligence test questions. At the "develop" stage, small group trials were conducted with three mathematics teachers and five students in class XI. Furthermore, a product revision was carried out, which was then the product of the revised result, which tested again in a large group, namely the class XI students of SMK Islam Madani consisting of 25 people. Finally, in the "disseminate" stage, socialization was carried out with mathematics teachers at the school where the researcher took the subject. The population in this study are mathematics teachers and students of class XI SMK Islam Madani, Kab. Tasikmalaya, West Java, with three mathematics teachers and 25 students of class XI majoring in Multimedia as the subjects. The research instruments used in this study were Teacher and Student Response Questionnaires and Visual Spatial Intelligence Test Questions.  The results showed that the comic learning media is in the category suitable for use by students, with the calculation of the teachers’ and student's response questionnaires having very good interpretations. Furthermore, the quality of the effectiveness of the visual-spatial intelligence of students after using comics learning media on geometry material gets a value of 1.58 with the "strong effects" criteria so that the SAC-assisted comic learning media is effectively used in learning.